Odpowiedzi

2010-01-30T10:04:19+01:00
2x + 9y= -9=>x=(-9-9y)/2
-3(-9-9y)/2+3y= 8/*2
27+27y+6y=16
33y=-11/33
y=-⅓
x=(-9+9*1/3)/2=-3

x - y = 0=>x=y
x + y +z =4
x + 2y +3z = 9

x=y
2x+z=4=>z=4-2x
x+2x+3(4-2x)=9
-3x=-3/(-3)
x=1
y=1
z=4-2=2

-2x + y = 0/*3=>-6x+3y=0 sumujemy oba
3x - 3y =1
-3x=1/(-3)
x=-⅓

-⅓*3 -3y=1
-3y=2/(-3)
y=-2/3
Najlepsza Odpowiedź!
2010-01-30T10:09:09+01:00
Układy równań metoda podstawiania:
1.

2x + 9y = -9
-3x+3y = 8

2x + 9y = - 9
3y = 8 + 3x

2x + 3(8 + 3x) = - 9
3y = 8 + 3x

2x + 24 + 9x = - 9
3y = 8 + 3x

11x = -33
3y = 8 + 3x

x = - 3
3y = 8 + 3x

x = - 3
3y = 8 + 3( -3)

x = - 3
3y = 8 – 9

x = - 3
3y = -1

x = - 3
y = -1/3

2.

x - y = 0
x + y +z =4
x + 2y +3z = 9

x = y
z = 4 – x – y
x + 2y +3z = 9

x = y
z = 4 – x – y
y + 2y + 3(4 – y – y) = 9

x = y
z = 4 – x – y
3y + 12 – 6y = 9

x = y
z = 4 – x – y
-3y = -3

x = 1
z = 4 – 1 – 1
y = 1

x = 1
z = 2
y = 1


Metodą przeciwnych współczynników:
1.

-2x + y = 0
3x - 3y =1

-6x + 3y = 0
3x – 3y = 1
- 3x = 1

3x = -1

x = -1/3

y = 2x
y = - 2/3

x = -1/3
y = - 2/3
2 4 2